The Interaction of Job Stress, Work-Family Conflict, Workload, and Social Support in Predicting Employee Burnout: Evidence of Mediation by Resilience - DJ, Yunni Rusmawati; Setyanti, Sri Wahyu Lelly Hana; Handriyono; Prihatini, Dewi (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Burnout is a serious problem in the banking sector, especially for back office employees who face high work demands, administrative accuracy, and regulatory compliance. This study aims to analyze the effects of work stress, work-family conflict, workload, and social support on burnout, and examine the role of employee resilience as a mediating variable. The study used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The study sample was back office employees at a state-owned bank in East Java. The results showed that work stress and work-family conflict had a positive and significant effect on burnout. Social support had a negative and significant effect, while workload had no significant effect on burnout. In the mediation model, resilience was unable to mediate the relationship between work stress and work-family conflict on burnout. However, resilience was shown to significantly mediate the relationship between workload and burnout, but did not mediate the effect of social support on burnout. These findings indicate that burnout in back office employees of state-owned banks is more influenced by psychological pressure and role demands than by workload factors. Therefore, organizations need to strengthen stress management strategies, provide consistent social support, and develop resilience-building programs to minimize the risk of burnout and improve employee well-being